2015
DOI: 10.12715/har.2015.4.39
|View full text |Cite
|
Sign up to set email alerts
|

Mild cognitive impairment: A comprehensive review

Abstract: Mild cognitive impairment (MCI) represents an intermediate stage between normal cognitive changes associated with aging and dementia. Individuals with MCI have been identified as having a faster rate of progression to dementias. Risk factors for progression include greater cognitive deficits at baseline, ApoE4 carrier status, brain volume changes, cerebrospinal fluid (CSF) changes, and the presence of behavioral and psychological symptoms. Refinements in the diagnostic criteria for MCI and the identification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Some participants mentioned that the dancing ameliorated their pain; however, more thought that it exacerbated their pain. Participants dropped from the program between a range of sessions (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Other reasons why participants dropped from the program were schedule conflicts, 1 participant thought the dance sessions were too difficult, and another participant left the country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some participants mentioned that the dancing ameliorated their pain; however, more thought that it exacerbated their pain. Participants dropped from the program between a range of sessions (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Other reasons why participants dropped from the program were schedule conflicts, 1 participant thought the dance sessions were too difficult, and another participant left the country.…”
Section: Discussionmentioning
confidence: 99%
“…6 Interventions that slow cognitive decline among persons with MCI are critical in order to prevent or delay conversion to AD. 6 Evidence indicates that pharmacological interventions in individuals with MCI have had little/no significant benefit in delaying the progression to AD 7 ; however, participation in physical activity (PA) has been shown to improve cognitive function in older adults with MCI. 8 Numerous studies have found that PA can improve chronic diseases and cognition.…”
Section: Introductionmentioning
confidence: 99%
“…This scale resembles the current MCI concept but is not identical to it. 10 It was Petersen who in 1999 refined the concept and started its current use. 6,10 Regarding this definition, MCI was first described as the initial stage of AD.…”
Section: Historicmentioning
confidence: 99%
“…10 It was Petersen who in 1999 refined the concept and started its current use. 6,10 Regarding this definition, MCI was first described as the initial stage of AD. It was characterized predominantly by a decline in memory more than that expected for a specific age but not yet sufficient for the diagnosis of dementia.…”
Section: Historicmentioning
confidence: 99%
See 1 more Smart Citation